2014
DOI: 10.1007/s11356-014-3316-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Pseudomonas aeruginosa from a virgin Brazilian Amazon region with potential to degrade atrazine

Abstract: The use of pesticides to increase agricultural production can result in the contamination of the environment, causing changes in the genetic structure of organisms and in the loss of biodiversity. This practice is also inducing changes in the rainforest ecosystem. In this work, a Pseudomonas aeruginosa isolated from a preservation soil area of the Brazilian Amazon Forest, without usage of any pesticide, was evaluated for its potential to degrade atrazine. This isolate presented all responsible genes (atzA, atz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Martin-Laurent et al (2003) showed that the atrazine-degrading community rapidly increased in the presence of atrazine and may be regarded as an opportunistic microbiota. Furthermore, the atrazine degrader Pseudomonas was isolated from Amazon Forest soil with no history of pesticide use (Fernandes et al, 2014). In contrast, Kersantè et al (2006) suggested that a treatment with atrazine did not significantly affect atzA, atzB, or atzC gene abundance in soil samples with no bioaugmentation.…”
Section: Discussionmentioning
confidence: 98%
“…Martin-Laurent et al (2003) showed that the atrazine-degrading community rapidly increased in the presence of atrazine and may be regarded as an opportunistic microbiota. Furthermore, the atrazine degrader Pseudomonas was isolated from Amazon Forest soil with no history of pesticide use (Fernandes et al, 2014). In contrast, Kersantè et al (2006) suggested that a treatment with atrazine did not significantly affect atzA, atzB, or atzC gene abundance in soil samples with no bioaugmentation.…”
Section: Discussionmentioning
confidence: 98%
“…For isolation, an evaluation of the growth and degradation of fipronil adapted from a medium (ATZ-R) is described by Fernandes et al without a nitrogen source (NH 4 NO 3 ) being used. 42 The culture medium consisted of 1 mol L −1 KH 2 PO 4 (67.0 mL L −1 ), 0.7 mol L −1 sodium citrate (2.0 g L −1 ), 1.0 mol L −1 of CaCl 2 •2H 2 O (0.2 mL L −1 ), and salt R solution (5 mL L −1 ). For solid medium, 2% bacteriological agar was added.…”
Section: Culture Media and Reagentsmentioning
confidence: 99%
“…The R salt solution was prepared as follows: MgSO 4 •7H 2 O (80.0 g L −1 ), FeSO 4 •7H 2 O (2.0 g L −1 ), and HCl (4.0 mL L −1 ). The glucose (0.2 g L −1 ) used by Fernandes et al 42 it was not used in present medium. The pH was adjusted to 6.8 and the medium was autoclaved at 121 °C for 20 min using fipronil as the sole nitrogen source (0.6 g L −1 ) (Badische Anilin & Soda Fabrik, BASF (Ludwigshafen am Rhein, Alemanha); 92.8% purity).…”
Section: Culture Media and Reagentsmentioning
confidence: 99%
“…These concentrations might still be relevant for human and ecosystem health (Shipitalo and Owens, 2003;Jablonowski and Schäffer, 2011;Vonberg et al, 2014). This persistence is surprising, given that studies have confirmed 1) the frequent presence of bacterial strains able to completely degrade atrazine (under controlled conditions) (Udikoviç- Koliç et al, 2012;Fernandes et al, 2014;Ehrl et al, 2018b;Kundu et al, 2019); and 2) alternative photolytic degradation of atrazine in soil (Kiss et al, 2007;Kiss and Virág, 2009;López-Muñoz et al, 2011). The persistence of atrazine and other pesticides in natural environments demands a better understanding of degradation processes to improve long-term monitoring and pollution mitigation strategies (Chow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%